PENERAPAN METODE “KB BERSYARAT” UNTUK MENCIPTAKAN SUASANA BERIMBANGBERBICARA DALAM PEMBELAJARAN BERDISKUSI PADASISWA KELAS XI MULTIMEDIA (MMD) SMKNEGERI 5 JEMBER - Supprapti, Muara (Jurnal Pengembangan Pendidikan, 2013)
Abstract. This study comes from the background ofthe need to increase the students’ active participation in learning discussionat Indonesian language subject, so that there are no more students who arepassive (only being the audience) and there are no more students who dominatethe discussion activity. The subject of the study is the eleventh gradestudents of Multimedia study program which is called MMD in this study in2012/2013 academic year. “KB Bersyarat” learning method (Conditioned SpeakingCard) is a learning method which uses learning cards with special conditions.These conditions enable students to have balanced situation in speaking. It isadapted the learning model so-called Time Token Arend 1997. In fact, by usingthis method, there is the increasing of the number of students who becomeactively participating in speaking, whether in questioning and or deliveringtheir opinions during the discussion in the class. Meanwhile, before using thismethod, there are only 36,47% of 36 students being active in the classicaldiscussion class. And then, the number of active students increases to57,32% at the first cycle of this method(KB Bersyarat, in groups). Fortunately, the number of active students issignificantly increasing to 86,50% at the second cycle of this method (KBBersyarat, individual work). Keywords: Balancedsituation in speaking, “KB Bersyarat” learning method.